Obesity Awareness and its Relationship to Sociodemographic Characteristics of Filipino Adults: A Survey among Work-From-Home Employees in Metro Cebu, Philippines - Gatillo, Jan Louie; Corpuz, Ariane; Leyco, Theresa; Ponce, Alexphil (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objective. Awareness and substantial understanding of obesity are essential components in its prevention and treatment. This study aimed to determine the degree of obesity awareness and its relationship to various sociodemographic characteristics among Filipino adults working from home (WFH). Methodology. This is a cross-sectional survey conducted in Metro Cebu, Philippines. Included were non-healthcare WFH professionals aged 18-64. Researcher-made Obesity Awareness Questionnaire (OAC-20) was used. Results. A total of 458 employees participated in the study; mean age was 30.33 years (SD=6.96), mostly female (71.40%) and majority single (77.07%). The mean obesity awareness score was 79.18% (SD=9.02). Age (p=0.198), BMI (p=0.397), work hours/day (p=0.101), and hours of physical activity/day (p=0.458) were not associated with obesity awareness. Similarly, male vs. female (p=0.515), and single vs. married respondents (p=0.629) did not differ significantly in terms of average scores. However, higher educational attainment (p=0.044) and higher socio-economic status (p=0.002) were significantly associated with higher obesity awareness scores. Conclusion. The surveyed WFH adults were aware of the majority of the important concepts on obesity. Educational attainment and socio-economic status were significant determinants of obesity awareness.